2021
DOI: 10.3390/pr9071086
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel for Breast Cancer Treatment-Side Effects on Ocular Surface, a Systematic Review

Abstract: Docetaxel is a very effective chemotherapeutic agent for the treatment of metastatic or locally advanced breast cancer. Epiphora (hyperlacrimation) has been shown to be the most common eye condition in patients receiving docetaxel-based chemotherapy. This symptom does not decrease visual acuity, but decreases the quality of life. Daily activities (reading, working on the computer, watching TV, and so on) are affected, with patients complaining about an alteration of daily life with the appearance of this sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…DTX is a highly effective chemotherapy drug derived from plants and is used to treat various cancers, including breast cancer, head and neck cancer, stomach cancer, prostate cancer, and non-small-cell lung cancer. [122][123][124][125] However, commercial formulations of DTX have limited ability to cross the blood-brain barrier (BBB). Additionally, the use of DTX is restricted by its various side effects, such as nephrotoxicity, allergic reactions, decreased white blood cell count, neurotoxicity, and fluid retention.…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…DTX is a highly effective chemotherapy drug derived from plants and is used to treat various cancers, including breast cancer, head and neck cancer, stomach cancer, prostate cancer, and non-small-cell lung cancer. [122][123][124][125] However, commercial formulations of DTX have limited ability to cross the blood-brain barrier (BBB). Additionally, the use of DTX is restricted by its various side effects, such as nephrotoxicity, allergic reactions, decreased white blood cell count, neurotoxicity, and fluid retention.…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…Several authors described the occurrence of narrowing and/or obstruction of the nasolacrimal canaliculus in breast cancer patients undergoing docetaxel treatment [18][19][20]. Additionally, studies have shown that epiphora (excessive tearing) is more prevalent in patients receiving weekly docetaxel treatment compared to those on a three-week treatment schedule [21,22].…”
Section: Mitotic Inhibitorsmentioning
confidence: 99%
“…Notably, bioactive glass (BG) is commonly used in orthopedics and dentistry. It is chosen as a vehicle for drug delivery due to its excellent biocompatibility, bioactivity, and significant tumor growth inhibition properties. Chemotherapy drugs, including nabumetone, paclitaxel, cyclophosphamide, docetaxel, epirubicin, paclitaxel analogues, and PARP inhibitors, are administered using the bionanosystem for breast cancer treatment. To develop novel therapeutic approaches, tubercidin (Tub), a well-known nucleoside, can undergo different metabolic reactions.…”
Section: Introductionmentioning
confidence: 99%